Activated biocarbons derived from molasses as new tailored CO2 adsorbents - Kiełbasa, Karolina (Frontiers in Chemistry, 2023)
An innovative and cost-effective method for enhancing CO2 capture by modifying the textural properties of derived activated biocarbons was explored. A molasses solution was prepared with a sucrose concentration of 1 mol/dm3. A two-step synthesis process was involved, which includes the hydrothermal synthesis of spherical carbonaceous materials from molasses followed by chemical activation. The carbonaceous material to activation agent ratio was studied from 1 to 4. The CO2 adsorption of all activated biocarbons was tested at 0, 10, and 20°C and a pressure of up to 1 bar. The results showed a significant correlation between CO2 adsorption and the textural properties of the activated biocarbons. The activated biocarbon with the highest CO2 adsorption of 7.1 mmol/g at 1 bar and 0°C was successfully produced by modifying with KOH. The selectivity of CO2 over N2 calculated on the basis of the Ideal Adsorbed Solution Theory was excellent (16.5). The Sips model was found to be the most suitable, and the isosteric heats of adsorption were also specified.